In this body : Kaqchikel Maya and the grounding of spirit - Hinojosa, Servando Z., 1968- (University of New Mexico Press, 2015)
"The Kaqchikel Maya, who live in the highlands of central Guatemala, experience soul as part of a continuum of bodily states. This account of life in one highland Maya community shows how, among Kaqchikels, spirit expresses itself fundamentally through the body, and not as something entirely separate from the body. By examining the lived-meanings of midwifery, soul therapy, and community dance in the town of San Juan Comalapa, the book identifies the body as the primary vehicle for spiritual grounding in daily life. Hinojosa invites readers to understand how specialists in these activities articulate their knowledge of the spirit through their understanding of blood, and he encourages readers to glimpse the hidden life of the body and how bodily processes guide local understandings of spirit at the personal and group level. This work further illuminates the agentive role of the body in Maya spiritual experience and enriches the current discussions of Maya spiritual revitalization"--